KONSEP ETIKA PESERTA DIDIK KETIKA BELAJAR DALAM KITAB TA’LIM AL-MUTA’ALLIM TARIQ AL-TA’ALLUM KARYA SYAIKH AL-ZARNUJI - Ahmad Sulaiman (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
Students are one component of education. Students have the potential to be developed to become established. While the factors that can develop students' self potential are themselves and their additional factors relating to parents, environment and education. Islamic education has the task of creating students to understand the purpose of attracting and understanding their work on earth. Because the education received is not only theoretical and dogmatic, but also recognition of the conceptual. Especially things related to life ethics must be owned by these students. Can be considered about ethics that can be done easily, then comes the ethical concepts of students as outlined in the discussion or ideas about matters related to the ethics of students expressed by many Muslims, one of which is the author of the book Ta'lim al-Muta ' allim Tariq al-Ta'allum, Burhanuddin al-Zarnuji. This research is a qualitative descriptive study with the type of literature study, with primary data sources Ta'lim al-Muta'allim Tariq al-Ta'allum by al-Zarnuji, and supported by secondary data sources such as journals, magazines and data discussed about the theme written in this article. The results of this study are expected to be able to arouse Muslim awareness and adjust the appropriateness of Islamic education leaders and inspire more complex and integral research on learner ethics.